2021
DOI: 10.3390/d13020049
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Epiphyte Assemblages on Isolated Trees along an Elevational Gradient in Southwest Panama

Abstract: Ongoing destruction of tropical forests makes isolated pasture trees potentially important for the persistence of original forest dwellers such as many vascular epiphytes. We studied epiphyte assemblages on 100 isolated trees at ten pasture sites in southwest Panama along an elevational gradient ranging from 140 to 1240 m a.s.l. We analysed epiphyte species composition (richness, similarity) and registered climate and host trait variables of potential influence on their occurrence. We found a total of 5876 epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…On the one hand, climate differences at a regional scale act as environmental filters to constraint epiphyte community assembly. For example, the typical elevational changes in epiphyte species composition were found to be explained by humidity gradients, as species richness showed mid-elevational peaks which corresponded to humidity gradients (Song et al, 2015a;Quiel and Zotz, 2021). A study from the temperate oceanic climate zone of Western Europe revealed that annual rainfall and average temperature gradients are responsible for the frequency and abundance of epiphytes (Klinghardt and Zotz, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, climate differences at a regional scale act as environmental filters to constraint epiphyte community assembly. For example, the typical elevational changes in epiphyte species composition were found to be explained by humidity gradients, as species richness showed mid-elevational peaks which corresponded to humidity gradients (Song et al, 2015a;Quiel and Zotz, 2021). A study from the temperate oceanic climate zone of Western Europe revealed that annual rainfall and average temperature gradients are responsible for the frequency and abundance of epiphytes (Klinghardt and Zotz, 2021).…”
Section: Introductionmentioning
confidence: 99%